Objectification on the difference between sex and sexism - Paasonen, Susanna 1975-; Attwood, Feona 1964-; McKee, Alan; Mercer, John 1966-; Smith, Clarissa (Routledge, Taylor & Francis Group, 2021)
This is a concise and accessible introduction into the concept of objectification, one of the most frequently recurring terms in both academic and media debates on the gendered politics of contemporary culture, and core to critiquing the social positions of sex and sexism.Objectification is an issue of media representation and everyday experiences alike. Central to theories of film spectatorship, beauty fashion and sex, objectification is connected to the harassment and discrimination of women, to the sexualization of culture and the pressing presence of body norms within media. This concise guidebook traces the history of the term’s emergence and its use in a variety of contexts such as debates about sexualization and the male gaze, and its mobilization in connection with the body, selfies and pornography, as well as in feminist activism.It will be an essential introduction for undergraduate and postgraduate students in Gender Studies, Media Studies, Sociology, Cultural Studies or Visual Arts
Keywords: Sozialpsychologie; Sexismus; Medien; Sexualisierung; Entmenschlichung; Kultur